Diskursus Kajian Gender Dalam Kitab Suci al-Qur'an - Masykuroh, Siti (Universitas Islam Negeri Raden Intan Lampung, 2018)
The focus of this study is a study of the theme of the theme presented by the Qur'an about the status and role of women and how to interpret these themes when projected in the frame of gender equality and equality. This research is purely biblical, the data is extracted from books, Tafsir ayat al-Qur'an and al-Hadiś as the main and first source. The analysis used in this study is a gender perspective. To sharpen analysts, social theories are also used, such as; class analysis, cultural analysis and discourse analysis. From the results of the study it was found that the themes displayed by the Qur'an revolved around the theme of the creation of men and women, equality of men and women, leadership, inheritance rights and polygamy. The discussion on the theme of the theme can be understood that the ideal of the Qur'an is actually the upholding of human life that is virtuous and respects universal human values (universal humanism). The universal humanitarian principles are manifested in efforts to uphold justice, equality, togetherness, and respect for the rights of others that are universally applicable.